Pyrolytic conversion of coconut oil fatty acids into industrial solvents - David, Renato M.
Using a factorial experiment design, the effects of catalyst type and catalyst concentration on the pyrolytic conversion of coconut oil fatty acids into industrial solvents were studied. Results of the pyrolysis of fatty acids at 345°C and 200 psig for 21 hours using each of the following compounds as catalysts in quantities amounting to 1%, 5% and 10% of the total charge: FeCl3, lava, AlCl3, and Al203, indicated that the type of catalyst that was used affected the solvent yield significantly while the catalyst concentrations that were used did not. Further statistical analysis using Duncan's multiple range test revealed that FeCl3 was the best catalyst, being significantly different from Al203, lava and Alcl3 which were not significantly different from one another. Duncan's test likewise confirmed the result that the catalyst concentrations that were used had no significant effect on the solvent yields. The mechanism for converting coconut oil fatty acids into industrial solvents has been postulated to involve the conversion of fatty acids to hydrocarbons followed by the latter's subsequent cracking. This mechanism satisfactorily accounts for the gases and distillate products that were obtained during the study.